A Paleomagnetic Inspection of the Paleocene-Eocene Thermal Maximum (PETM) in the Southern Pyrenees - Oliva-Urcia, Belén; Gil-Peña, Inmaculada; Samsó, José M.; Soto, Ruth; Rosales, Idoia (Frontiers in Earth Science, 2018)
Magnetic properties of rocks can be useful for determining paleoenvironmental changes. A dramatic climate change that occurred in the Paleocene-Eocene Thermal Maximum (PETM) modified the environment and, hence, the magnetic properties recorded in the sediments. New paleomagnetic data from marine records of the PETM in the Southern Pyrenean zone displays a variation of the magnetic parameters in four different sections. The magnetic signal reveals a positive excursion of magnetic values starting before the onset of the marly interval of La Faja de las Flores Mb (beginning of the PETM record, Ilerdian) in the Carriata section with a maximum value in the marly interval. A similar magnetic signal is observed in the Bujaruelo section ( 10 km south of Carriata at PETM times) that is related directly to the marly interval of Faja de las Flores Mb. However, towards the south, the PETM interval does not appear in the sedimentary record; therefore, in the southern Gallisué section, no magnetic excursion occurs. In the southernmost-studied Entremón section, a positive magnetic excursion occurs in a thin marly interval unrelated to the PETM, and in two lower intervals of the column. All sections were later subjected to deformation during the pyrean orogeny and the three northernmost sections in the regional cleavage front, where pressure solution and remagnetizations have been described. A post-folding remagnetization component is found in the three northern sections.